2020
DOI: 10.1016/j.jhydrol.2020.125079
|View full text |Cite
|
Sign up to set email alerts
|

Well productivity in the Ponta Grossa dike Swarm, Brazil: An integrated study with magnetic data inversion and clustering analysis of model solutions

Abstract: Well productivity in the Ponta Grossa Dike Swarm, Brazil: An integrated study with magnetic data inversion and clustering analysis of model solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
0
11
1
3
Order By: Relevance
“…Previous work has also similarly assessed the contribution of intrusions to well productivity (Chevallier et al 2004;Matter et al 2006;Mohamed et al 2015). Although median values around 700 m in the present study are almost double the values found in Cavalcante et al (2020),…”
Section: Oriented Magnetic Gradients (Omgs)contrasting
confidence: 42%
See 1 more Smart Citation
“…Previous work has also similarly assessed the contribution of intrusions to well productivity (Chevallier et al 2004;Matter et al 2006;Mohamed et al 2015). Although median values around 700 m in the present study are almost double the values found in Cavalcante et al (2020),…”
Section: Oriented Magnetic Gradients (Omgs)contrasting
confidence: 42%
“…The mapped GMOs were able to elucidate regional geological structures that extend into the subsurface and semi-quantitative methods were able to estimate their depths. Cavalcante et al (2020) mapped NW-SE dykes in the northwestern portion of the CBAS with depths averaging around 300 m, whose wells mostly located close to this depth do not reach this depth, but their productivity was justified by the authors as being influenced by primary damage zones caused by the instrumentality of these dikes, allowing the wells to be fed not directly by the dikes, but by the structures associated with them. Previous work has also similarly assessed the contribution of intrusions to well productivity (Chevallier et al 2004;Matter et al 2006;Mohamed et al 2015).…”
Section: Oriented Magnetic Gradients (Omgs)mentioning
confidence: 99%
“…In addition, the relative crustal extension can be estimated by calculating the sum of the dikes' widths from a prole taken perpendicularly to the dike swarm divided by the total prole length (Castro et al, 2008). On the other hand, width and depth to the top can aect the circulation and ow of groundwater and hydrocarbon in several ways, such as compartmentalization, obstruction, and providing preferential pathways (Cavalcante et al, 2020). As McGrath and Hood (1970) pointed out, the depth to the top z 0 can be estimated independently on geological or magnetization directions assuming the dike model.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…24) than in the source location (x 0 , z 0 ). Our study area is located in the Ponta Grossa Arch (PGA), southern Brazil, which has been the subject of several recent studies (e.g., Strugale et al, 2007;Gomes et al, 2011;Louro et al, 2019;Cavalcante et al, 2020).…”
Section: R a F Tmentioning
confidence: 99%
“…For two-dimensional (2D) sources, ASA (Li, 2006) and AMA (Liu et al, 2015) are invariant with magnetization direction, further simplifying the interpretation of elongated anomalies and magnetic lineaments from dike swarms. Depending on their properties and geometry, such tabular features may have a significant impact on subsurface conditions including the flow regime and exploration for groundwater resources (Cavalcante et al, 2020).…”
Section: Introductionmentioning
confidence: 99%